Indebted : How Families Make College Work at Any Cost - Zaloom, Caitlin (Book collections on Project MUSE., 2019)
This book breaks through the culture of silence surrounding the student debt crisis, revealing the unspoken costs of sending our kids to college. It describes the profound moral conflicts for parents as they try to honor what they see as their highest parental duty--providing their children with opportunity--and shows how parents and students alike are forced to take on enormous debts and gamble on an investment that might not pay off.